Sustainable software solutions: a tool integrating life cycle analysis and ISO quality models - Qiang, Yang; Che Pa, Noraini; Ismail, Rosli (Insight Society, 2024)
Sustainability is essential in software systems in today's eco-conscious atmosphere. However, companies often overlook this, resulting in energy waste and e-waste. We implemented an automated software sustainability assessment solution to address this by fusing Life Cycle Analysis (LCA) and ISO quality model implementation capabilities. Our tool reduces environmental impact, promotes economic, technical, environmental, and social sustainability, improves resource labor efficiency and usage time (hardware life), and enables user autonomy. Developed in Python, it is a tool for assessing and evaluating software sustainability (such as performance or maintainability) that has been validated in real-world scenarios. We provide a method for assessing software maintainability and energy efficiency by combining LCA with the ISO 25010 standard. Case studies confirm that the new tool offers a comprehensive sustainability assessment method consistent with sustainable development goals. The study results show that maintainability and energy efficiency were thoroughly assessed. The accuracy and precision of the test assessment results were further confirmed, indicating that the tool is consistent across different software projects and reliable, proving its practical application. This advancement is essential for sustainable software development and provides concrete metrics and operational insights for developers and their companies. In future research, we plan to extend the tool's metric scope and improve data visualization/information customization suitable for more diverse software environments and sustainability goals. Our tool promotes eco-responsibility while raising quality and sustainability standards for all software systems.